Solid medical waste: a cross sectional study of household disposal practices and reported harm in Southern Ghana - Emilia Asuquo Udofia; Gabriel Gulis; Julius Fobil (BMC Public Health, 2017)
Abstract Background Solid medical waste (SMW) in households is perceived to pose minimal risks to the public compared to SMW generated from healthcare facilities. While waste from healthcare facilities is subject to recommended safety measures to minimize risks to human health and the environment, similar waste in households is often untreated and co-mingled with household waste which ends up in landfills and open dumps in many African countries. In Ghana, the management of this potentially hazardous waste stream at household and community level has not been widely reported. The objective of this study was to investigate household disposal practices and harm resulting from SMW generated in households and the community. Methods A cross-sectional questionnaire survey of 600 households was undertaken in Ga South Municipal Assembly in Accra, Ghana from mid-April to June, 2014. Factors investigated included socio-demographic characteristics, medication related practices, the belief that one is at risk of diseases associated with SMW, SMW disposal practices and reported harm associated with SMW at home and in the community. Results Eighty percent and 89% of respondents discarded unwanted medicines and sharps in household refuse bins respectively. A corresponding 23% and 35% of respondents discarded these items without a container. Harm from SMW in the household and in the community was reported by 5% and 3% of respondents respectively. Persons who believed they were at risk of diseases associated with SMW were nearly three times more likely to report harm in the household (OR 2.75, 95%CI 1.15–6.54). Conclusion The belief that one can be harmed by diseases associated with SMW influenced reporting rates in the study area. Disposal practices suggest the presence of unwanted medicines and sharps in the household waste stream conferring on it hazardous properties. Given the low rates of harm reported, elimination of preventable harm might justify community intervention.